Chemical attributes of Oxisol in no-tillage system fertilized with manure from cattle and mineral fertilizers - Barcellos, Milena; Motta, Antonio Carlos Vargas; Pauletti, Volnei; da Silva, José Carlos Peixoto Modesto; Barbosa, Julierme Zimmer (Comunicata Scientiae, 2015)
Organic fertilization in no-tillage system (NTS) has been used in regions milk production, in an order to provide nutrients for crops and provide a destination for high production of animal waste. The aim of this study was to evaluate the chemical attributes of an Oxisol, a function of organic fertilization with liquid manure from dairy cattle (LMDC) and mineral fertilizers. The experiment was conducted under NTS with crop rotation including legumes and grasses. The treatments were distributed in three randomized blocks with factorial arrangement, using three levels of mineral fertilizer (0, 50 and 100 % of the dose recommended for the crops) and four levels of organic fertilizer (0, 30, 60 and 90 m3 ha-1year-1). After six years of fertilizer management of crops, soil was collected from five depths (0-0.05, 0.05-0.10, 0.10-0.30, 0.30-0.50 e 0.50-0.80 m). The samples were determined the chemical pH, H++Al3+, Al3+, Ca2+, Mg2+, K+,electrical conductivity (EC), bases saturation (V), Ca2+/Mg2+ ratio, total organic C (TOC), B, Cl, Fe, Cu, Zn and Mn. The mineral fertilizers acidify the soil, raised the K+, P and EC and, changed the Zn and Cu contents. The organic fertilization with LMDC was a source of nutrients (Ca 2+, Mg2+, K+, P, Zn and Cu), raised the TOC and the EC, and kept the soil acidity attributes (pH, H++ Al3+ and V).